Diagnostic Performance Addition of Abnormal P Wave Dispersion on Moderate Risk Duke Treadmill Score Criteria in Detecting Severe Stenosis of Coronary Arteries in Stable Angina Pectoris Patients - Widodo Darmo Sentono; Erika Maharani; Irsad Andi Arso (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2015)
Background: Moderate risk Duke treadmill score (DTS) in threadmill test (TMT), needs additional diagnostic tool to increase its sensitivity of detecting severe coronary artery stenosis in patients with stable angina pectoris. A P wave dispersion (PWD) during TMT currently has a significant relationship with DTS value and can increase the sensitivity in identifying an ischemia. This studyaimed to investigate whether the addition of PWD in moderate risk DTS can improve the prediction of the severity of coronary artery stenosis in patients with stable angina pectoris. Methods: This study is a diagnostic test with cross-sectional design. The subjects were patients who had undergone TMT and coronary angiography at the Dr. Sardjito General Hospital Yogyakarta. The outcomes were sensitivity and specifi city of abnormal PWD in moderate risk DTS patients for predicting the severe stenosis in those with stable angina pectoris as compared with moderate risk DTS and normal PWD.Results: The additional of PWD at moderate risk DTS on 64 subjects had a sensitivity of 86.7%, a specifi city of 44.1%, a positive predictive value of 57.8%, a negative predictive value of 79.0%, a positive likelihood ratio of 1.6, a negative likelihood ratio of 0.3 and a prevalence of 46.9%, witha prediction accuracy of 64.1%. Conclusion: The additional of abnormal PWD in moderate risk DTS had a sensitivity of 86.7% and a specificity of 44.1% for severe coronary artery stenosis in patients with angina pectoris.Keywords: P wave dispersion, moderate risk Duke treadmill score, severe coronary stenosis.